Beauty Boarding and the Dhaka-Based Bengali Intelligentsia: Constructing Memory, Consumerism and Identity - Talukder, Tusar; Mithun, Liton Chakraborty (SCHOLARS: Journal of Arts & Humanities, 2025)
Beauty Boarding holds a unique place in Dhaka’s cultural history. Dubbed as Dhaka’s answer to Kolkata’s Coffee House, the establishment offers both dining and lodging facilities. The once vibrant informal literary gatherings spearheaded by many prominent Bengali modernist poets and writers and attended by a group of budding poets and writers regularly for a decade have provided the aura and ethos to the selfhood of the place. However, a massacre of many people by the Pakistani army and their collaborators at Beauty Boarding in the 1971 Liberation War of Bangladesh has made it part of the country’s national history. Consequently, this space carries many memories, most of which have cultural and historical value. By drawing on insights from Halbwachs’s theory of “collective memory,” Lefebvre’s “social production of space,” de Certeau’s “practice of everyday life,” and the concept of “commodification of memory,” this paper investigates how an interplay of memory, space, and culture is central to the identity of Beauty Boarding and how the authority concerned utilises its cultural capital to advance its business interests. It also highlights how a large part of Dhaka-based intelligentsia forms its identity based on its interaction and negotiation with the cultural history of the place.